Two-Stage Over-the-Air (OTA) Test Method for LTE MIMO Device Performance Evaluation - Ya Jing; Xu Zhao; Hongwei Kong; Steve Duffy; Moray Rumney (International Journal of Antennas and Propagation)
With MIMO technology being adopted by the wireless communication standards LTE and HSPA+, MIMO OTA research has attracted wide interest from both industry and academia. Parallel studies are underway in COST2100, CTIA, and 3GPP RAN WG4. The major test challenge for MIMO OTA is how to create a repeatable scenario which accurately reflects the MIMO antenna radiation performance in a realistic wireless propagation environment. Different MIMO OTA methods differ in the way to reproduce a specified MIMO channel model. This paper introduces a novel, flexible, and cost-effective method for measuring MIMO OTA using a two-stage approach. In the first stage, the antenna pattern is measured in an anechoic chamber using a nonintrusive approach, that is without cabled connections or modifying the device. In the second stage, the antenna pattern is convolved with the chosen channel model in a channel emulator to measure throughput using a cabled connection.